Modified Endoscopic Ultrasound Needle to Obtain Histological Core Tissue Samples: A Retrospective Analysis - Munish Ashat; Kaartik Soota; Jagpal S. Klair; Sarika Gupta; Chris Jensen; Arvind R. Murali; Randhir Jesudoss; Rami El-Abiad; Henning Gerke (Korean Society of Gastrointestinal Endoscopy, 2020)
Background/Aims Endoscopic ultrasound (EUS)-guided fine-needle aspiration is very effective for providing specimens for cytological evaluation. However, the ability to provide sufficient tissue for histological evaluation has been challenging due to the technical limitations of dedicated core biopsy needles. Recently, a modified EUS needle has been introduced to obtain tissue core samples for histological analysis. We aimed to determine (1) its ability to obtain specimens for histological assessment and (2) the diagnostic accuracy of EUS-guided fine-needle biopsy (EUS-FNB) using this needle. Methods We retrospectively analyzed consecutive cases of FNB using modified EUS needles for 342 lesions in 303 patients. The cytology and histological specimens were analyzed. Diagnostic accuracy was calculated. Results Adequate cytological and histological assessment was possible in 293/342 (86%) and 264/342 (77%) lesions, respectively. Diagnostic accuracy of the cytological specimen was 294/342 (86%) versus 254/342 (74%) for the histological specimen (p<0.01). Diagnostic accuracy of the combined cytological and histological assessment was 323/342 (94.4%), which was significantly higher than that of both histology alone (p<0.001) and cytology alone (p=0.001). Conclusions EUS-FNB with the modified EUS needle provided histologic tissue cores in the majority of cases and achieved excellent diagnostic accuracy with few needle passes.